Pollution havens: International empirical evidence using a shadow price measure of climate policy stringency - Erik Hille (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Given the ambiguous empirical results of previous research, this paper tests whether support for a climate policy induced pollution haven effect and the pollution haven hypothesis can be found. Unlike the majority of previous studies, the analysis is based on international panel data and includes several methodological novelties: By arguing that trade flows of dirty goods to less polluting sectors may also be influenced by changes in policy stringency, trade information on primary, secondary, and tertiary sectors are included. In order to clearly differentiate between dirty sectors and sectors with high pollution abatement costs, separate measures for pollution intensity and policy stringency are implemented. For the latter an internationally comparable, sector-specific measure of climate policy stringency is derived using a shadow price approach. Endogeneity between a country s trade openness and its trade flows is addressed by estimating a gravity-based instrumental variable. The results provide evidence for a stronger pollution haven effect regarding carbon dioxide intensive and emission relevant energy intensive sectors. However, the impact of climate policy on polluting sectors seems to be rather limited as a distinct pollution haven effect for gross energy intensive sectors cannot be found. Similarly, no support for the stronger pollution haven hypothesis is revealed.
Keywords: F18; Q54; D24; 330